Estudio técnico financiero para la creación de una agrohostería en la provincia de Manabí, Cantón Pedernales, Parroquia Cojimíes - Andrade España, Mayra Dudey (2007)
Tourism is an activity that is becoming increasingly important in the world, to become one of the main economic activities in all countries, especially those with significant cultural monuments, beautiful landscapes or geographic resources and ecological. Existing biodiversity worth admiring in our country is impossible not to exploit the tourist track. In our country tourism activities understood as: accommodation, food and beverage, transportation, operations, brokerage, casinos, gambling halls have increased, according to the Ministry of Tourism in a 4.80% in the last 10 years in virtue foreign exchange income from this area varies between 250 million and 447 million annually whose value is increased from 3.96% to 4.92% and in places of employment generation in the different tourist services.